Molecular Mechanics and Semi-empirical Analyses of the Interaction between Cu(II) and Amino Acids in Solution - Huq, Fazlul (Asian Journal of Chemistry, 2016)
The interaction between Cu2+ and amino acids viz., glycine, L-histidine and L-arginine, in solution has been investigated by UV-Visible spectrophotometry using the technique of continuous variation and molecular modeling. For each metal ion and amino acid combination, absorbance values at lmax were plotted against concentrations of reactants. The maxima in the absorbance vs. concentration graphs gave the ratios at which the metal ions and amino acids combined. Copper(II) is found to form predominantly 1 : 3 complex with glycine, 1 : 4 complex with L-histidine and 1 : 2 complex with L-arginine. As expected, the d-d absorption bands due to copper(II) have been found to show a shift to shorter wavelengths when complexed with glycine, L-histidine and L-arginine. The proposed structures of the complexes have been optimized and their electronic spectra generated based on molecular mechanics and semi-empirical calculations. Comparison of the observed and predicted electronic spectra suggested the most likely structures present in solution.